Solar bioreactors used for the industrial production of microalgae - Masojídek, Jiří; Lhotský, Richard; Štěrbová, Karolína; Zittelli, Graziella Chini; Torzillo, Giuseppe (Applied microbiology and biotechnology, 2023)
Microalgae are excellent sources of biomass containing several important compounds for human and animal nutrition-proteins, lipids, polysaccharides, pigments and antioxidants as well as bioactive secondary metabolites. In addition, they have a great biotechnological potential for nutraceuticals, and pharmaceuticals as well as for CO2 sequestration, wastewater treatment, and potentially also biofuel and biopolymer production. In this review, the industrial production of the most frequently used microalgae genera-Arthrospira, Chlorella, Dunaliella, Haematococcus, Nannochloropsis, Phaeodactylum, Porphyridium and several other species is discussed as concerns the applicability of the most widely used large-scale systems, solar bioreactors (SBRs)-open ponds, raceways, cascades, sleeves, columns, flat panels, tubular systems and others. Microalgae culturing is a complex process in which bioreactor operating parameters and physiological variables closely interact. The requirements of the biological system-microalgae culture are crucial to select the suitable type of SBR. When designing a cultivation process, the phototrophic production of microalgae biomass, it is necessary to employ SBRs that are adequately designed, built and operated to satisfy the physiological requirements of the selected microalgae species, considering also local climate. Moreover, scaling up microalgae cultures for commercial production requires qualified staff working out a suitable cultivation regime. KEY POINTS: • Large-scale solar bioreactors designed for microalgae culturing. • Most frequently used microalgae genera for commercial production. • Scale-up requires suitable cultivation conditions and well-elaborated protocols.
Keywords: biotechnologie; Chlorophyceae; Chlorella; Large-scale production; Biotechnology; Solar bioreactor; bioreaktory; zvířata; Humans; Biomass; mikrořasy; Bioreactors; Microalgae; Biofuels; biopaliva; lidé; biomasa; Animals